Pengaruh Tingkat Stress Kerja terhadap Kinerja Karyawan Bandar Udara Sepinggan Balikpapan - Hamidah, Firda Nur; Azhar, Herida Panji Olivia (Sekolah Tinggi Teknologi Kedirgantaraan, 2024)
With the increasing workload and demands in the aviation industry, it is important to understand how job stress affects productivity and work effectiveness. This study examines the effect of job stress levels on employee performance at Sepinggan Balikpapan Airport. The study was conducted by distributing questionnaires to 45 employees from various airport divisions. The results were then processed using a t-test and approached using simple linear regression. The results showed that job stress was negatively related to employee performance. It is hoped that the results of this study will provide insight for management in designing effective stress mitigation strategies.